Efficacy and mechanism of retinyl palmitate against UVB-induced skin photoaging - Shu, Peng; Li, Menggeng; Zhao, Nan; Wang, Yuan; Zhang, Lanyue; Du, Zhiyun (Frontiers in Pharmacology, 2023)
Retinyl palmitate (RP) is a vitamin A derivative that has been widely used in anti-aging and skin treatment. The aim of this study is to investigate the effect of RP on UVB (Ultraviolet radiation B) induced photoaging and its potential mechanism. Immunofluorescence assay demonstrates that RP can reduce collagen degradation in skin cells by UVB radiation and reduce apoptosis of skin cells. Cell migration assay reveals that RP can increase cell migration rate, helping to repair skin damage and restore cell viability. Immunohistochemical assays indicate that RP can significantly reduce the expression of IL-6, IL-1β, TNF-α induced by UVB radiation. Moreover, metabolomics and transcriptomics results suggest that RP regulates several metabolic pathways and gene expression, particularly in inflammatory signaling pathways, collagen synthesis and apoptosis, exhibiting significant regulatory effects. Furthermore, network pharmacological analysis predicts that RP may affect UVB-induced photoaging by regulating multiple key proteins and signaling pathways. Overall, this study demonstrates that RP has significant anti-photoaging ability, acting through several pathways including inhibition of inflammatory response, promotion of collagen synthesis and inhibition of apoptosis. These results provide a scientific basis for the application of RP in skin anti-photoaging and therapy, enabling the potential usage of RP to skin care products.